2008
DOI: 10.1002/jrs.1852
|View full text |Cite
|
Sign up to set email alerts
|

Aperture based Raman spectroscopy on SiGe film structures with high spatial resolution

Abstract: We have investigated silicon-germanium (SiGe) line structures employing metallic apertures in combination with Raman spectroscopy to obtain high-spatial strain resolution below the diffraction limit. The apertures were cut into specifically shaped electrochemically etched tungsten tips, which were adjusted within the Raman laser beam on the sample surface by a tuning fork atomic force microscope. With this setup, line structures on patterned SiGe films with a center-to-center distance down to 200 nm were resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…Raman spectra of the Ge x Si 1– x samples were measured and are shown in Figure . The broad bands correspond to the expected values for the homogeneous bond vibrations in Si and Ge at 521 and 298 cm –1 , respectively. For the intermediate Ge x Si 1– x phases, characteristic bands of Si–Si, Si–Ge, and Ge–Ge vibrations are present . When the Ge content increases, the Si–Si vibration band shifts to lower frequencies (from 521 to 490 cm –1 ), and when the Si content increases, the Ge–Ge vibration band also shifts to lower frequencies (from 298 to 275 cm –1 ).…”
Section: Resultssupporting
confidence: 60%
“…Raman spectra of the Ge x Si 1– x samples were measured and are shown in Figure . The broad bands correspond to the expected values for the homogeneous bond vibrations in Si and Ge at 521 and 298 cm –1 , respectively. For the intermediate Ge x Si 1– x phases, characteristic bands of Si–Si, Si–Ge, and Ge–Ge vibrations are present . When the Ge content increases, the Si–Si vibration band shifts to lower frequencies (from 521 to 490 cm –1 ), and when the Si content increases, the Ge–Ge vibration band also shifts to lower frequencies (from 298 to 275 cm –1 ).…”
Section: Resultssupporting
confidence: 60%
“…155 SNOM was applied for Raman microscopy on dyes, 135 thin films, 158,161 and semiconductors such as SiGe. 157 Lines of various widths etched in SiGe by focused ion beam were imaged by SNOM and a lateral resolution of 200 nm was achieved. 157 SNOM can deliver spatial resolution at the nanoscale, but the technique suffers from the low signal collected, particularly for Raman spectroscopy.…”
Section: Scanning Near-field Optical Microscopy (Snom) With Aperturementioning
confidence: 99%
“…157 Lines of various widths etched in SiGe by focused ion beam were imaged by SNOM and a lateral resolution of 200 nm was achieved. 157 SNOM can deliver spatial resolution at the nanoscale, but the technique suffers from the low signal collected, particularly for Raman spectroscopy. 155,162 The light transmission coefficient through an aperture in a conducting plane was predicted to depend on the aperture diameter a and the wavelength λ as (a/λ) 4 .…”
Section: Scanning Near-field Optical Microscopy (Snom) With Aperturementioning
confidence: 99%
“…The practical application of the technique is illustrated on a silicon-on-insulator (SOI) microelectronic structure. Mai et al [240] have employed metallic apertures in combination with Raman spectroscopy to obtain high-spatial strain resolution below the diffraction limit. With this set-up, which uses apertures cut into specifically shaped and electrochemically etched tungsten tips, the authors investigated line structures on patterned silicon-germanium films and showed that their set-up has a large potential for further near-field Raman applications.…”
Section: Special Raman Techniques and Methods Including Ters And Datamentioning
confidence: 99%